Evaluation of coverage and compliance to mass drug administration for lymphatic filariasis elimination in two endemic districts of Karnataka - Shivalingaiah, Anwith H.; K., Ravikumar; Gurupadaswamy, Sunil M. (International Journal Of Community Medicine And Public Health, 2019)
Background: Lymphatic filariasis is a debilitating and disfiguring disease causing significant socioeconomic burden. India is endemic for filariasis which includes Kalaburagi and Yadgir districts in Karnataka. India has the target for filariasis elimination by 2020 and mass drug administration [MDA] is a strategy for elimination. The objective of the study was to evaluate the coverage and compliance of mass drug administration against lymphatic filariasis. Methods: The study was a cross sectional study conducted during the month of October 2018 in Kalaburagi and Yadgir districts. The study subjects included all the residents of cluster except subjects aged below 2 years and pregnant women. Multi stage sampling was used and three clusters from rural area and one cluster from urban area from each district. Data collection was done by household survey after informed consent using a standard questionnaire. Results: A total population of 1,963 subjects residing in 399 houses of two districts was included. Majority of the study subjects 1517 (77.27%) were in the age group of more than 15 years with predominantly males 984(50.12%). The coverage rate and compliance rate of MDA was 83.17% and 92.46% in Kalaburagi district and 86.71% and 86.98% in Yadgir district respectively. The effective coverage rate and coverage compliance gap was 76.89% and 7.53% in Kalaburagi district, 75.42% and 13.01% in Yadgir district. Incomplete dose of MDA was consumed by 17 subjects in Kalaburagi district and 21 subjects in Yadgir district. Conclusions: The effective MDA coverage in both the study districts is below 85% which is not satisfactory.